Modelling Customers Response to Service offers using game Theory Case Study; MTN and Vodafone in Bolgatanga Polytechnic - Issahaku, Abdul-Majeed (2016)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy (Mathematics), Faculty of Physical Sciences, College of Science. November 2011.